Karakteristik Ibu dan Kehamilan Risiko Tinggi Berhubungan dengan Anemia pada Ibu Hamil di wilayah kerja Puskesmas Sangkulirang, Kabupaten Kutai Timur Tahun 2025 - Sumiarti; Eka Frenty Hadiningsih; Hestri Norhapifah; Ida Hayati (Poltekkes Kemenkes Kupang, 2026)
Background: Anemia in pregnant women remains an important public health problem because it contributes to an increased risk of pregnancy complications, hemorrhage, low birth weight, prematurity, and maternal and infant mortality. World Health Organization reported that the global prevalence of anemia among pregnant women is still around 36.5%, while in Indonesia the prevalence of anemia among pregnant women remains high based on national data and continues to be one of the priorities in maternal health problems. This condition is also still found in the working area of Puskesmas Sangkulirang. Objectives: This study aimed to analyze the relationship between maternal characteristics and high-risk pregnancy with the incidence of anemia among pregnant women. Methods: This study employed an analytic observational design with a cross-sectional approach. The sample consisted of 47 third-trimester pregnant women selected using an accidental sampling technique. Data were collected through questionnaires, observation sheets, and hemoglobin level examinations, then analyzed using Fisher’s Exact Test with a significance level of 5%. Results: The results showed that most respondents were not anemic, totaling 30 respondents (63.8%). The majority were aged 20–35 years, totaling 25 respondents (53.2%), multiparous, totaling 20 respondents (42.6%), and unemployed, totaling 30 respondents (63.8%). In addition, most respondents were categorized as having low-risk pregnancies, totaling 19 respondents (40.4%). Bivariate analysis showed significant relationships between maternal age and anemia incidence (p=0.001), parity and anemia incidence (p=0.017), employment status and anemia incidence (p=0.026), as well as high-risk pregnancy and anemia incidence (p=0.013). Conclusion: These findings indicate that maternal characteristics and pregnancy risk factors play important roles in the incidence of anemia among pregnant women. Therefore, efforts to improve early detection and prevention through nutritional education and continuous monitoring of risk factors are necessary.